2017
DOI: 10.1002/arch.21427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis provides insights of anti‐insect molecular mechanism of Cassia obtusifolia trypsin inhibitor against Pieris rapae

Abstract: Pieris rapae, a serious Lepidoptera pest of cultivated crucifers, utilizes midgut enzymes to digest food and detoxify secondary metabolites from host plants. A recombinant trypsin inhibitor (COTI)1 from nonhost plant, Cassia obtusifolia, significantly decreased activities of trypsin-like proteases in the larval midgut on Pieris rapae and could suppress the growth of larvae. In order to know how COTI took effect, transcriptional profiles of P. rapae midgut in response to COTI was studied. A total of 51,544 unig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The gut is the first defence barrier against pathogens and toxins acquired through food [2,62]. Well-characterized families of enzymes that play crucial roles in detox pathways, such as GST, UGT, and CYP proteins and peroxidases, were identified as DEGs here and in previous studies on Lepidoptera [9,12,46,61,63,64]. Most of these gene families have variable expression profiles; some transcripts are overexpressed in sugarcane-fed larvae and others overexpressed in artificial diet-fed larvae, probably due to the high structural and functional diversity of these families (Fig 5).…”
Section: Detoxificationmentioning
confidence: 74%
See 3 more Smart Citations
“…The gut is the first defence barrier against pathogens and toxins acquired through food [2,62]. Well-characterized families of enzymes that play crucial roles in detox pathways, such as GST, UGT, and CYP proteins and peroxidases, were identified as DEGs here and in previous studies on Lepidoptera [9,12,46,61,63,64]. Most of these gene families have variable expression profiles; some transcripts are overexpressed in sugarcane-fed larvae and others overexpressed in artificial diet-fed larvae, probably due to the high structural and functional diversity of these families (Fig 5).…”
Section: Detoxificationmentioning
confidence: 74%
“…saccharalis . Tissue-specific transcriptomes of other lepidopterans have shown that despite the high variability in contig numbers, the number of protein-coding unigenes is consistently between 20,000 and 30,000 [ 9 , 12 , 46 48 ]. Insect transcriptomes have been sequenced at higher frequency in the last five years, proving to be useful as a descriptive tool and an invaluable source of sequences for studies researching gene function and design of RNAi experiments [ 2 , 10 , 13 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Storage organs of plant such as seeds, tubers and also leaves, flowers, and fruits contain different types of protease inhibitors (PIs) which is able to inhibit some enzymes like trypsin, pepsin and chymotrypsin [9,10,7,11]. PIs are small proteins or peptides that inhibit the catalytic action of proteases by forming stoichiometric and stable complexes with their proteolytic enzymes blocking or altering the active site [11][12][13]. Protease inhibitors in legume seed can inhibit pancreatic serine proteases, thus slowing down protein digestion at the small intestine [14,15].…”
Section: Introductionmentioning
confidence: 99%